Uniform and nonuniform staggering of wage contracts - Leif Danziger (Institute for the Study of Labor (IZA), 2010)
This paper provides a model that can account for the almost uniform staggering of wage contracts in some countries as well as for the markedly nonuniform staggering in others. In the model, short and long contracts as well as long contracts concluded in different periods are strategic substitutes, which provides a powerful rationale for staggering. We show that for realistic parameter values, there is a continuum of possible equilibria with various degrees of staggering of long contracts. If the contracting cost is not too large, then the lowest possible degree of staggering decreases with the contracting cost and increases with monetary uncertainty.
Keywords: E31; E32; J41; 330; Uniform staggering; nonuniform staggering; monetary policy shocks; strategic substitutability; wage contracts; contract duration; Lohn; Arbeitsvertrag; Dauer; Lohnverhandlungstheorie; Spieltheorie; Substitutionseffekt; Geldpolitik; Schock; Theorie